Size Effect on Recycled Concrete Strength and Its Prediction Model Using Standard Neutrosophic Number - X. Peng; Q. W. Yang; F. J. Qin (Advances in Civil Engineering)
In recent years, research on recycled aggregate concrete has become a hot issue in the field of civil engineering. This paper mainly studies the size effects on compressive and tensile strengths of the recycled aggregate concrete. Firstly, four sets of recycled concrete cube specimens with different sizes are produced in the laboratory. Secondly, the experiments on compressive and tensile strengths are carried out to obtain the rules of the strength value with the change of the specimen size. Thirdly, a standard neutrosophic number is proposed and used in modelling the size effect law more reasonably. According to the experimental results, it was found that the compressive and tensile strengths of recycled concrete both have obvious size effects. In general, the strength value decreases gradually with the increase of specimen size. Using the standard neutrosophic number, the proposed new formula on size effect law is more suitable for tackling the indeterminacy in the experimental data. It has been shown that the size effect law based on the standard neutrosophic number is more realistic than the existing size effect law. The results may be useful for the engineering application of the recycled concrete and can be extended to other types of size effect laws in the future.